Struktur Komunitas Gastropoda Pada Ekowisata Hutan Mangrove di Kecamatan Weda Halmahera Tengah - Ilham Madjid; Hasna Ahmad (Peneliti.net, 2022)
Mangrove is a term for tropical coastal communities which are dominated by several types of mangroves. One of the eco-mangroves in Indonesia is the Nusliko Mangrove Forest. This study aims to determine the type, diversity and environmental parameters that affect the existence of gastropod tourism in mangrove forest ecotourism. The research took place from April to May 2021, the object of research was gastropods in the mangrove forest ecotourism in Nusliko Village, Weda District, Central Halmahera. The method used in this research is quantitative. The study used a 1x1 m plot that was placed uniformly. The gastropods contained in the observation plots were determined by species and the number of individuals of each species was counted. The data were analyzed using the Shannon-Wiener diversity index. The results showed that there were 3 families and 5 species of gastropods on transect I, while on transect II there were 3 families and 3 species. The diversity of gastropod species on transect I is H' = 1.121 medium category, while the diversity of species on transect II is H' = 0.65 low category. Environmental parameters on transect 1 air temperature 310C normal category, air salinity 30%o brackish category, water pH 8.2 alkaline category and the substrate is mud, while at station II air temperature 300C normal category, water salinity 30%o brackish category, pH 8 ,5 categorize the base and the substrate is sandy mud.